The Systemic Host Modulation Therapy of Periodontal Diseases - Hasanain H Shakir; Maha A Aziz (College of Dentistry/ University of Baghdad, 2016)
Background: The systemic host modulation therapy is new approach in treatment of periodontal diseases. Materials and methods:The target of this treatment is the host response to microbial infection because at present time,it is well known that most of damage found in periodontal diseases cause by the inflammatory -immune response to periodontal infections.Sub-antimicrobial-dose Doxycycline (SDD) is a 20-mg dose of Doxycycline (Periostat) that is approved and indicated as an adjunct to scaling and root planning (SRP) in the treatment of chronic periodontitis. Results:At present, SDD (Periostat) is the only systemically administered agent that is approved by the U.S. Food and Drug Administration (FDA) and accepted by the American Dental Association (ADA).